A designer's guide to asynchronous VLSI - Beerel, Peter A. (Cambridge University Press, 2010)
"Bypass the limitations of synchronous design and create low power, higher performance circuits with shorter design times using this practical guide to asynchronous design. The fundamentals of asynchronous design are covered, as is a large variety of design styles, while the emphasis throughout is on practical techniques and real-world applications"--Provided by publisher.
Keywords: Integrated circuits -- Very large scale integration -- Computer-aided design.; Integrated circuits -- Very large scale integration -- Design and construction.; elektronické knihy; electronic books